INVESTIGATION AND DESIGN OF AN ACTIVE CELL BALANCING SYSTEM FOR LI-ION BATTERIES - Karabeyoğlu, Enver Derun; Güzel, Eda; Kılıç, Halis; Sarioglu, Baykal; Gökdel, Yiğit Dağhan; Serincan, Mustafa (My University, 2019)
A type of active battery cell balancing system based on buck-boost converters isproposed in this study. By using equivalent circuit model of the battery cells,proposed active balancing circuit is examined in detail. An algorithm is developedto actively control the balancing operation. The algorithm is also utilized to preventany failures in the balancing operation. The proposed system is simulated under lowand heavy load. The simulation results indicates that 25 mV imbalance betweenpotentials of two battery cells can be balanced out in approximately 147 secondsunder low load and in 127 seconds under high load.
Keywords: Mühendislik; Elektrik ve Elektronik; Enerji ve Yakıtlar